Clinical Implication of Cervical Pain on Posture among Teaching Professionals Aged Between 25-35 Years- A Cross Sectional Study: Life Sciences-Physiotherapy - Kataria, Jyoti; Sindhu, Bijender; Pawaria, Sonia (International Journal of Life Science and Pharma Research, 2022)
Cervical pain is amongst the incessant musculoskeletal disorders having a prevalence of 30% up to 60 % among teaching professionals. Cervical pain also known as neck pain; have consequences which are very severe among several working populations. Primary objective of study was to find out consequences of cervical neck pain on scapula position. Present study will embrace us about clinical implications of cervical pain on static scapular position further significant positive result lead to formation of specific scapular rehabilitation program for teaching professionals keeping all risk factors and their work ergonomics. Cross-sectional Comparative study design was used to identify the effect of cervical pain over resting position of scapula position with respect to scapula protraction and scapula upward rotation among 107 school teachers further to mention it is an extension of research work of primary author on school teachers. Scapula protraction was assessed at three different positions i.e at rest, 45-degree shoulder flexion and 90-degree glenohumeral abduction and scapula upward rotation was examined with the help of baseline digital inclinometer at four different positions. Results exhibit changes in scapula protraction and upward rotation among school teachers keeping p value < 0.001. Since school teachers primarily work on computer screen for teaching and preparation of lesson plans, this executes enormous load on teachers as they have to work continuously in static cervical posture for long hours continuously which executes significant load on neck and scapulothoracic musculature and alters the mechanics cervical pain results in statistically significant changes in scapula position i.e., scapula protraction, and scapula upward rotation in primary school teachers in all examined positions.